The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.22236/arkesmas.v4i2.3788
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Perilaku Sadari Remaja Putri Dalam Upaya Deteksi Dini Kanker Payudara

Abstract: ABSTRACT The prevalence of breast cancer continues to increase by 1.4 per 1,000 population and cause of death number 7 (5.7%) from all causes of death Since 2007-2013 early detection of breast cancer has been carried out by women as many as 644,951 people (1.75%) with the discovery of a lump suspect (tumor) 1682 people or 2.6 per population. Where as SADANIS (Clinical Breast Check) program showed an increase to (57%) to 1,623,913 people from 904,099 at the end of 2014. The purpose of this research is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Measurement of attitude variables using the Guttman scale. Fill out a questionnaire consisting of 10 statements with two categories, namely "Correct" is given a score of one (1) and "False" is given a score (0) (10). Respondents' exposure to information about BSE through the internet, mass media, health workers, family, friends, and others.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of attitude variables using the Guttman scale. Fill out a questionnaire consisting of 10 statements with two categories, namely "Correct" is given a score of one (1) and "False" is given a score (0) (10). Respondents' exposure to information about BSE through the internet, mass media, health workers, family, friends, and others.…”
Section: Methodsmentioning
confidence: 99%
“…Breast cancer (Carcinoma mammae) is a condition in which cells have lost control of their normal mechanisms, resulting in abnormal, rapid and uncontrolled growth in breast tissue. At first, breast cancer attacked women over 30 years old, but now the age of people living with breast cancer has shifted to women who are young or teenagers (1). Cancer incidence is increasing yearly and occurs almost all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…The chi-square test using Fisher's Exact with a significance of 5% shows a p-value of 0.001, so it can be concluded that there is a relation between the perceived severity of breast cancer and BSE on the practice of BSE. 14 Many female students believe that breast cancer with late detection will not increase the risk of death; breast cancer cannot spread to other body tissues. Also, patients with late-stage breast cancer can still carry out their daily activities usually.…”
Section: Relation Between Perceived Severity Of Breast Cancer and Bse...mentioning
confidence: 99%
“…16,17 However, although female teenagers may feel the high benefits of BSE, they do not necessarily want to do it because someone who thinks that the benefits derived from BSE practice are less than the barriers to BSE, then the person likely does not give a positive response to BSE practice. 14 Compared with the Health Belief Model theory, who feels confident about the perceived benefits makes someone want to do preventive behavior, including BSE. In addition to the Health Belief Model theory, it also states that if an individual who has a firm belief in a vulnerability and also seriousness to a disease is not necessarily willing to take the recommended preventive action unless the person believes that the act reduces the threat or can provide benefits to the community.…”
Section: Relation Of Perceived Benefit On Bse Practice With Bse Pract...mentioning
confidence: 99%
“…Kanker merupakan pertumbuhan abnormal sel jaringan tubuh yang berubah menjadi tumor ganas (Tania et al, 2019). Kanker payudara adalah penyakit dimana selsel kehilangan mekanisme Kontrol normalnya yang mengakibatkan pertumbuhan jaringan payudara yang abnormal, cepat dan tidak terkendali (Afianty et al, 2019). Kanker payudara juga merupakan pembunuh wanita nomor satu (Nainggolan, 2020).…”
Section: Pendahuluanunclassified